PENGEMBANGAN E- MODUL BERBASIS FLIP BOOK PADA MATA PELAJARAN CHASSIS DAN PEMINDAH TENAGA SISTEM REM PESERTA DIDIK KELAS XI TEKNIK KENDARAAN RINGAN SMK NEGERI 1 SAGARANTEN KABUPATEN SUKABUMI - Permana, Asep; Ibdalsyah, Ibdalsyah; Hartono, Rudi (JURNAL TEKNOLOGI PENDIDIKAN, 2025)
This study aims to develop a Flip Book-based E-Module as an interactive learning medium for the subject of Chassis and Power Transmission Brake Systems for Grade XI students majoring in Light Vehicle Engineering at SMK Negeri 1 Sagaranten, Sukabumi Regency. The development addresses the challenges of vocational education, which is still dominated by conventional methods and lacks instructional media capable of presenting technical content visually and engagingly. The research employed a Research and Development (R&D) method by combining the ADDIE and Dick & Carey instructional design models. The development stages included needs analysis, design, prototype development, expert validation, and limited trials with students. The validation results from subject matter experts, media experts, and instructional design experts showed that the developed E-Module is highly feasible for use, with respective validation scores of 92%, 93%, and 94%. Small- and medium-group trials also demonstrated positive student responses, with feasibility scores of 89% and 91%, respectively. Furthermore, the effectiveness test using pre-test and post-test methods indicated a significant increase of 55% in students' learning outcomes after using the Flip Book-based E-Module. These findings confirm that the Flip Book-based E-Module is not only feasible but also effective in enhancing the quality of vocational learning. The product is expected to serve as an alternative digital learning medium that supports the implementation of the Merdeka Curriculum. Additionally, this digital module has the potential to strengthen students’ digital literacy and independent learning in the era of Education 4.0.